Changes in physicomechanical, nutritional, and sensory indicators of taro tubers at different harvest times - LOI, Nguyen Van; BINH, Pham Thi; SAM, Vu Kieu (Food Science and Technology, 2023)
Taro tuber, which has the scientific name of Colocasia esculenta, is grown in Vietnam. The nutritional compositions of taro tuber are mostly starch, vitamin, protein, lipid, cellulose, and mineral. The purpose of this study was to determine the changes in physicomechanical, nutritional, and sensory indicators of taro tubers at different harvest times. The physicomechanical, nutritional, and sensory indicators of taro tubers were determined at three harvesting stages of 280, 300, and 320 days. As a result, the right time to harvest taro tubers is 300 days or more because taro tubers have fully developed in terms of size, weight, nutritional composition, and sensory indicators by this time. Specifically, at 300 days, taro tubers had a diameter of 5.6 cm and a weight of 71 g, with 69.83% water, 26.17% glucid, 2.82% protein, and 0.32% lipid. At the time of harvest of 300 days, 14 amino acids were identified, including 7 essential amino acids, namely, leucine, isoleucine, lysine, methionine, valine, phenylalanine, and histidine. Through the analysis of sensory indicators such as color, smell, taste, and texture of taro tubers, choosing the time to harvest taro tubers at 300 days for processing and storage is appropriate.